Pengaruh Return On Asset Dan Debt To Equity Ratio (DER) Terhadap Dividend Payout Ratio Pada PT Telkom Indonesia Periode 2015-2024 - Tasya Fitriyani; Waluyo Jati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study is to determine the significant effect between ROA and DER on DPR at PT Telkom Indonesia Tbk. The method in this study is a quantitative method. The population in this study is the financial statements at PT Telkom Indonesia Tbk. The sample used is the financial statements in the form of balance sheets and profit and loss for the period 2015-2024. The data analysis test in this study uses Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, R Determination Coefficient Test, Simple Linear Regression Analysis Test, Multiple Linear Regression Test, Hypothesis t Test, F Test (simultaneous) the results of this study are Leadership has a significant effect on DPR as indicated by the results of the hypothesis with a value of (2.013 <2.776) and a significant value greater than Sig. 0.05 or (0.79> 0.05), thus H01 is rejected and Ha1 is accepted this shows that there is a significant influence between ROA on DPR. Based on the results of hypothesis testing 2, the calculated t value is obtained > t table or (2,013 < 2.776) and the significant value is greater than Sig. 0.05 or (0.732 > 0.05) thus H02 is rejected and Ha2 is accepted, this indicates that there is a significant influence between DER on DPR. on the results of hypothesis testing 3, the calculated F value is obtained > F table or 355 < 2.776) and the significant value is greater than Sig. 0.05 or (0.732 > 0.05). Thus H03 is rejected and Ha3 is accepted, this indicates that there is a significant influence simultaneously between ROA and DER on DPR.